Shifting priorities and expectations in the new world of work. Insights from millennials and generation Z - Trifan, Vanina Adoriana; Pantea, Mioara Florina (Journal of Business Economics and Management, 2024)
In the contemporary world of work and modern business, the well-being of a company is directly linked with the well-being of its employees, and in this context, the proactive promotion of work-life balance has become more important than ever because it meets the new ideal and is an ongoing challenge through the lens of the younger generation’s age groups. By unpacking worklife balance into five drivers, the present paper aims to explore the recent trends, priorities, and expectations of the modern workforce. The target population was represented by two generations of employees, Millennials and Generation Z, and the research hypotheses were tested using structural equation in SmartPLS. The results of this research aim to enhance the current knowledge base, offering a distinct perspective along with significant findings for employers, managers, recruiters, policymakers, and other nodes of control who can gain insights regarding work-related priorities and expectations.